Sophia princess among beasts - Patterson, James (London : Arrow Book, 2020)
Sophia is smart, beautiful, and accomplished, a beloved princess devoted to the people and to reading books. The kingdom is hers, until she is plunged into a nightmarish realm populated by the awful beasts she read about as a child. The beasts are real. And so is the great army marching on her castle. The people look to Sophia for protection. They will all perish unless she can unlock an ancient secret as profound as life and death itself.
Adult
Keywords: Monsters Princesses Secrecy Young adult fiction Fantasy fiction Fiction; Juvenile literature